2017
DOI: 10.1108/ijpsm-04-2016-0065
|View full text |Cite
|
Sign up to set email alerts
|

Matrix organizations and cross-functional teams in the public sector: a systematic review

Abstract: Purpose The purpose of this paper is to review the empirical research on matrix organizations and cross-functional teams (CFTs) in the public sector, focussing on typical application areas and settings and on motivation for deployment and evidence of utility. Design/methodology/approach This is a systematic literature review compiled from several electronic databases. Data cover the period from 1990 to 2015 and are confined to academic articles written in English. Findings Applications of the matrix approa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 48 publications
(89 reference statements)
0
11
0
Order By: Relevance
“…Thus, unlike the existing approaches (Sharata, 2015;Pakarinen & Virtanen, 2017;Telizhenko et al, 2016), the mechanism of management of quality at the operational level of the university has been suggested; it is mainly focused on contact personnel and provides support of a high level of quality not through the procedure of the bureaucratic control, but through adaptability, counterweight system and self-regulation.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, unlike the existing approaches (Sharata, 2015;Pakarinen & Virtanen, 2017;Telizhenko et al, 2016), the mechanism of management of quality at the operational level of the university has been suggested; it is mainly focused on contact personnel and provides support of a high level of quality not through the procedure of the bureaucratic control, but through adaptability, counterweight system and self-regulation.…”
Section: Resultsmentioning
confidence: 99%
“…Power play and competition between departments may hinder individual team member commitment toward the CFT (Ghobadi and D'Ambra, 2012;Wong et al, 2009). Government administrations, in essence still structured and managed in bureaucratic ways, have been found to be more sensitive to the aforementioned issues (Pakarinen and Virtanen, 2017;Piercy et al, 2013). To our first perspective, the organization critic, the perceived lack of organizational support for knowledge sharing and integration in general leads to the perception that the importance of effective knowledge management is far from being shared by all team members.…”
Section: Discussionmentioning
confidence: 96%
“…Often-cited benefits of the use of CFTs are the enhanced quality of decision-making stemming from the diversity in perspectives, skills, information and resources (Gelderman et al, 2017;Ghobadi, 2011;Huang and Newell, 2003;Srikanth et al, 2016;Stipp et al, 2018); the improved communication of project information and the positive effect this has on organizational learning (Lopes Pimenta et al, 2014;Piercy et al, 2013;Stipp et al, 2018;Wang and He, 2008); and the all-round contribution to organizational performance in both the private and public sector (Daspit et al, 2013;Pakarinen and Virtanen, 2017;Piercy et al, 2013;Stipp et al, 2018). Unsurprisingly, functional diversity and the accompanying differences in perspectives also lead to a lot of problems within CFTs.…”
Section: Cross-functional Teamsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have suggested that well-designed collaborations within health care can improve patient care outcomes, 6-10 increase patient and provider satisfaction, 11 protect providers from burnout, 12,13 and lead to streamlined processes and improved use of resources. 9 In other industries, interprofessional teams have been shown to improve organizational performance, coordination, and internal collaboration, 14 as well as reduce costs. 15 In adding to this evidence base, researchers have an important opportunity to more comprehensively assess the impact of optimal IP-CLEs.…”
Section: Importance Of Leadership In the Macro Meso And Micro Envirmentioning
confidence: 99%